Salt Attack And Dampness Diagnoses Of Heritage Buildings In Penang, Malaysia - Rahman @ Drahman, Haris Fadzilah Abdul (2011)
Most conservation done in Malaysia focuses on old historical buildings not for adaptive re-use but mainly for exhibition and tourist attraction buildings and monuments. Conserving buildings for adaptive re-use is more challenging because many issues have to be taken into consideration for the conservation such as safety, comfort, durability, spatial requirements and usage; and aesthetic. This needs an in depth understanding of the building; not only in terms of its architectural values but also its state of dilapidation. Conservation in Malaysia is considered new compared to other countries, thus, there is not many research documentations and dilapidation reports done on methods and procedure for conservation in heritage building. Amongst the common conservation problems of heritage buildings, salt attack and rising damp are considered the most challenging to resolve.